Facilitare l’apprendimento dell’italiano L2 attraverso la danza di tradizione popolare - Pagan, Alessandra (Educazione Linguistica Language Education, 2018)
Motor skills such as sport and dance help trigger informal, experiential pathways of learning. In particular, a humanistic, glotto-pedagogical approach through traditional folk dance may facilitate the acquisition of an L2 level of Italian, thereby giving rise to a form ‘parallel learning’ in which determined linguistic formulations become immediately linked to the subject’s direct, physical, lived experiences (perceptions-actions) and fostering synergistic collaboration between the hemispheres of the brain (as occurs in Total Physical Response teaching methods). Psychomotor research provides further indications on the use choreographic action to facilitate the teaching of Italian as foreign language through slow-motion, emphatic movement and vocalization, and the use of rhetorical figures, especially metaphors and idiomatic expressions which describe and interpret movement. Additionally, linguistic studies structured in this way lead to an understanding of the importance of non-verbal aspect of communication for the full comprehension of the message being conveyed.